Impact of anaemia in oesophago-gastric cancer patients undergoing curative treatment by means of neoadjuvant chemotherapy and surgery. (September 2021) - Chan, Benson YL.; McKinlay, Sonya; Forshaw, Matthew; MacDonald, Andrew; Maitra, Rudra; Orizu, Mavis; McSorley, Stephen T.
Abstract: Background: The present study investigated factors associated with pre-neoadjuvant chemotherapy (NAC), and pre-operative anaemia, and examined their impact on outcomes in patients with oesophago-gastric cancer treated with curative intent. Methods: Patients diagnosed with oesophago-gastric cancer (January 2010 to December 2015) and treated with curative intent by NAC then surgery at a tertiary centre were included. Patients were grouped by the presence of anaemia (haemoglobin <130 mg/L in males and <120 mg/L in females) and into microcytic (MCV <80 fL), normocytic (80–100 fL) and macrocytic (>100 fL) subgroups. Categorical data were analysed by chi-squared test and overall survival by univariate and multivariate Cox regression. Results: 99/295 (34%) patients who received NAC were diagnosed with pre-NAC anaemia, and 157/268 (59%) of patients who subsequently underwent surgery were diagnosed with pre-operative anaemia. Normocytic anaemia was the most common, with 76 (26%) in pre-NAC and 107 (40%) in pre-operative groups. Pre-NAC anaemia was associated with increasing clinical N stage ( p = 0.022), higher modified Glasgow Prognostic Score (mGPS) ( p = 0.006), and a higher rate of intra-operative transfusion ( p = 0.030). Pre-operative anaemia was associated with pre-NAC anaemia (p = 0.004), increasing age ( p = 0.026), higher pre-operative mGPS ( p = 0.021), and a higher rate of intra-operative transfusion (p = 0.021). Anaemia before NAC and surgery was associated with poorer overall survival in patient following R0 resection, independent of stage (HR 1.26, 95% CI 1.02–1.54, p = 0.030). Conclusion: Anaemia was associated with poorer overall survival and greater requirement for intra-operative blood transfusion in oesophago-gastric cancer patients undergoing treatment with curative intent. Highlights: Pre-neoadjuvant chemotherapy and pre-operative anaemia was associated with poorer overall survival. Normocytic anaemia was most prevalent, suggesting a multifactorial aetiology. Targeting anaemia at this point in treatment may reduce blood transfusion and improve outcomes.